Ganga - "Hollick, Julian Crandall" (New Delhi, 2007)
Ganga has always been more than just an ordinary river. For millions of Indians, sheis also a goddess. Yet the river is exploited as much as she is worshipped. Her wateris siphoned off for irrigation, toxic chemicals are dumped into her, and dams and barrages have been built on her course causing immense damage. Ganga is in danger of dying - but if the river dies, will the goddess die too? The question took journalist julian crandall hollick on an extraordinary journey starting at gaumukh and endingat sagar island. Travelling mostly on small country boats, he discovered a river that most people simply do not know: A river that never remains the same, which is often abandoned, and at times is no more than a stream. Combining travelogue, science andhistory, ganga is a fascinating - and troubling - portrait of the river today. It willshow you ganga as you have never seen her before.
Keywords: Ganga